Highly efficient, ultralow turn-on voltage red and white organic light-emitting devices based on a novel exciplex host. Issue 11 (27th April 2021) - Song, Jian; Zhang, Fujun; Yang, Liping; Chen, Keming; Li, Asu; Sheng, Ren; Duan, Yu; Chen, Ping
Abstract : We have prepared high-performance white OLEDs based on exciplex systems and blue ultra-thin FIrPic layers, exhibiting a low turn-on voltage of 2.2 V with a maximum power efficiency of 34.1 lm W −1, and the CIE coordinate (0.33, 0.33) at 1000 cd m −2 . Abstract : The exciplex forming co-host is one of the most promising candidates for developing high-performance organic light-emitting devices (OLEDs) that can implement an internal quantum efficiency of 100%. In this work, a novel exciplex co-host system by employing N -([1, 1′-biphenyl]-2-yl)- N -(9, 9-dimethyl-9 H -fluoren-2-yl)-9, 9′-spirobi[fluoren]-4-amine (FSF4A) and 2, 4, 6-tris[3-(diphenylphosphinyl)phenyl]-1, 3, 5-triazine (PO-T2T) is applied to design simplified red and white OLEDs with low turn-on voltage and high efficiency. A high performance red phosphorescent organic light-emitting diode (PhOLED) is achieved by employing an exciplex co-host in a low guest doping level of 3%, showing the best performance with a maximum power efficiency of 38.5 lm W −1, a maximum external quantum efficiency of 17.3%, and an ultralow turn-on voltage of 1.95 V, respectively. Based on the red device, the ultra-thin FIrPic layer is inserted to achieve high performance white OLEDs, exhibiting a low turn-on voltage of 2.2 V with a maximum power efficiency of 34.1 lm W −1, and the Commission Internationale de'IEclairage (CIE) coordinate (0.33, 0.33) at 1000 cd m −2 . These superior properties can be attributed to reduced barriers and the effective energy transfer by employing an exciplex co-host.